Screen Time and Its Association with Sleep Disorders in Adults: A Cross-Sectional Study - Azad, Taqqadus; Khan, Muhammad Hadi; Sufyan Ullah, Muhammad; Chaudhry, Sarah; Ahmad, Hafiz Usama; Hijazi, Huzaifa (Indus Journal of Bioscience Research, 2025)
Background: Prolonged use of electronic devices has become a routine part of daily life and is increasingly recognized as a contributor to poor sleep health. Sleep disturbances linked to screen exposure are an emerging public health concern. Objective: To assess the association between screen time and sleep disorders among adults. Methods: A cross-sectional study was conducted from January 2024 to January 2025 on 82 adults at Services Hospital, Lahore. Data were collected using a structured questionnaire that included demographic characteristics, screen time patterns, and sleep-related variables. Standardized instruments such as the Pittsburgh Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS) were used. Statistical analysis was performed using chi-square tests and t-tests, with p < 0.05 considered significant. Results: The majority of participants (62.2%) reported poor sleep quality, while 35.4% slept less than six hours daily. Excessive screen exposure was strongly associated with disturbed sleep. Participants with more than six hours of daily screen use showed a 94.7% prevalence of poor sleep quality compared with 21.4% among those with less than two hours (p = 0.001). Smartphone use and pre-bedtime screen exposure were significantly correlated with delayed sleep onset and daytime sleepiness. Conclusion: Excessive screen time, particularly in the evening, is significantly associated with poor sleep quality and reduced sleep duration in adults. Reducing screen exposure before bedtime may help improve sleep hygiene and overall health.